Modelos estocásticos para análise e simulação de sequências hidrológicas - Olive, Dirceu Machado (1970)
The daily river flow sequences are stochastically analyzed and a subsequent simulation is made. Two models are developed. The first one, based on Time Series concepts, uses the modern techniques of Fast Fourier Transform (FFT) in harmonic analysis to obtain the deterministic component. This procedure constitutes a pioneer experience in the subject. The stochastic component is analysed as an autoregressive process. The second model uses Markov Chains concepts in which the daily flows are considered autocorrelated. Both models were tested using daily flow data of the Rio Grande river, before it meets with the Paraiba to form the Paraná river, in the gage called S. J. da Barra, and covers the period from 1/1/1941 to 22/2/1952 in a total of 4.374 consecutive days.